Optimization of exopolysaccharide production by pleurotus ostreatus using different cultivation strategies - Mohd. Helmi Johari Masri, 1988-, author; Hesham Ali Metwally Ali El-Enshasy, 1968-, supervisor; Fakulti Kejuruteraan Kimia dan Kejuruteraan Tenaga (2015)
Thesis (Sarjana Sains (Bioprosess)) - Universiti Teknologi Malaysia, 2015